Comparative Analysis of Expression of the Main Virulence Genes in Various Vibrio cholerae О1 Strains - N. B. Cheldyshova; Z. L. Devdariani (Проблемы особо опасных инфекций, 2022)
The aim of the work was a comparative study of the expression of the main virulence genes in Vibrio cholerae strains of the classical biovar, typical and genetically modified strains of V. cholerae, El Tor biovar.Materials and methods. Natural toxigenic strains of V. cholerae O1, classical biovar (J89, Pakistan, 1969), typical (M-887, Astrakhan, 1970) and genetically modified (301, Taganrog, 2011) strains of the El Tor biovar were used as model ones. The strains were grown under optimum conditions for the production of cholera toxin and toxin-coregulated pili. The assessment of strain growth was carried out in LB broth at room temperature with determination of the cells number on a Biowave DNA spectrophotometer (Biochrome Ltd., UK). Determination of gene expression was performed using real-time PCR with reverse transcription.Results and discussion. The expression of structural (ctxA, tcpA) and regulatory (toxR, toxT, tcpP, tcpH) virulence genes has been investigated in V. cholerae strains of the classical biovar, typical and genetically modified strains of the El Tor biovar. Significant differences have been revealed in terms of time and level of maximum expression of these genes in strains of classical and El Tor biovars. It was found that ctxA and toxR genes expression in the genovariant strain reached its maximum 1–3 h earlier than in the other strains. At the same time, the level of ctxA gene expression corresponded to the level of the classical strain. The maximum expression of the toxR gene in the genovariant strain was higher than in typical El Tor and classical strains, and also had a clear inverse correlation with ctxA gene expression. Expression of the tcpA, toxT, and tcpH genes in the classical biovar strain reached its maximum 1–2 h earlier than in the El Tor biovar strains. These differences should be taken into account when conducting research work related to the study of the expression of the main virulence genes.